2009
DOI: 10.2975/33.1.2009.38.46
|View full text |Cite
|
Sign up to set email alerts
|

Why and how people decide to stop taking prescribed psychiatric medication: Exploring the subjective process of choice.

Abstract: Implications of these findings are discussed, emphasizing the importance of the "doctor-patient" relationship context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(132 citation statements)
references
References 35 publications
(75 reference statements)
7
125
0
Order By: Relevance
“…Sideeffects of anti-psychotic medication can also lead to changes in both self-identity and selfesteem, often through weight gain and sexual dysfunction (Johnstone et al, 2009;Laithwaite et al, 2007;Roe et al, 2009). …”
Section: Sub-theme Ii: the Loss Of Selfmentioning
confidence: 99%
“…Sideeffects of anti-psychotic medication can also lead to changes in both self-identity and selfesteem, often through weight gain and sexual dysfunction (Johnstone et al, 2009;Laithwaite et al, 2007;Roe et al, 2009). …”
Section: Sub-theme Ii: the Loss Of Selfmentioning
confidence: 99%
“…Generally, research supports the view that medications decrease the severity of psychiatric symptoms (Roe et al, 2009). While medication does not cure symptoms, it does stabilize them (Allison, 2012).…”
Section: Bulletin Of the Menninger Clinicmentioning
confidence: 90%
“…Patients often mistake illness symptoms for side effects or they are overly preoccupied with side effects and thereby exacerbate them (Andreasson & Skarsater, 2012;Meehan, Sted-man, & Wallace, 2011). Roe et al (2009) reported that nonadherence can also result from disagreement between patient and provider. These points, and patient concerns about side effects, suggest the need for improved patient-provider communication about medications.…”
Section: Reasons Why Patients Won't Take Medicationsmentioning
confidence: 99%
See 2 more Smart Citations